Implementasi Hardware Redundancy Pada Sistem Monitoring Kebocoran Gas LPG Menggunakan Metode Hot Standby Non Detector - Deddy Aditya Kurniawan; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
LPG (Liquified Petroleum Gas) is a petroleum gas that is commonly used as fuel for gas stoves. From year to year the use of LPG has always increased, which is the risk of gas leakage will also increase. So it is necessary to reduce these risks, with create a system that can detect LPG gas leaks. The design of a gas leak detection system must have a high availability value, because when there is a crucial component damage it will cause an inaccurate reading. High availability systems can be achieved by implementing redundancies. In this research, one of the redundancy methods will be implemented, namely Hot Standby Redundancy in the gas leak monitoring system. The gas monitoring system will require gas sensors (MQ-2 and MQ-5) as inputs, Arduino as processors, buzzers and applications as output. While the components that are considered crucial are components or controllers. For the Hot Standby Redundancy redundancy method, it will make a duplicate controller and will always be active to monitor the condition of the main controller. The monitoring process will use I2C serial communication, by means of a backup (master) controller sending requests periodically to determine the condition of the master controller. Based on the tests that have been carried out, the implementation of the Hot Standby Redundancy mechanism in the LPG, downtime gas leak monitoring system both failover and failback is equal to 153.46 ms, with availability of 99.99%.